Navigating the Future of Logistics: A Narrative Review of Autonomous Freight Systems - Yosepha, Sri Yanthy (Logistica : Journal of Logistic and Transportation, 2025)
The adoption of autonomous vehicles in freight transport represents a transformative shift in global logistics. However, research remains fragmented regarding the balance between efficiency, sustainability, safety, and user acceptance. This narrative review synthesizes recent empirical studies to identify critical opportunities and challenges in autonomous freight systems. The findings indicate substantial efficiency and cost benefits, particularly through truck platooning and automated last-mile delivery solutions. Environmental outcomes are generally positive, though lifecycle trade-offs such as infrastructure wear and energy sources complicate sustainability claims. Safety concerns persist in mixed-traffic environments, where operational reliability and public trust remain unresolved. User acceptance is shaped by demographic and sectoral factors, with stronger receptivity in industries handling perishable or time-sensitive goods. The review highlights that adoption trajectories are contingent on systemic factors, including regulatory alignment, infrastructure readiness, and financing mechanisms. These insights underscore the need for adaptive policy frameworks, targeted training, and inclusive financing models to ensure that autonomous freight technologies enhance not only efficiency but also long-term sustainability and equity.